(untitled) (Bangladesh Veterinarian, 2011)
Fertility of Red Chittagong bulls (RCB) using Non-Return Rate (NRR), reproductive efficiency of Red Chittagong cows (RCC) using pregnancy rate and number of services per pregnancy and parasitic infestation of two different ages and sexes were studied. The NRR ranged from 53.1% to 70.6% with an overall mean of 63.9%. Overall pregnancy rate was 65.8% and about 1.4 services were required per pregnancy. Overall 47.7% animals were infested with parasites. Five species of parasites were detected in the faeces: Balantidium coli (40%), Paramphistomum spp (47.7%), Fasciola spp (5.8%), Coccidia spp (4.5%), and Moniezia spp (1.9%). The prevalence of parasites in animals over four years age was higher (P<0.05) than in animals below four years of age: the prevalence was higher in female than in male hosts (P>0.05). DOI: 10.3329/bvet.v27i2.7557 Bangl. vet. 2010. Vol. 27, No. 2, 74-81